Membangun Model Hubungan Persepsi dan Dinamika Kelompok terhadap Pelestarian Hutan dan Peningkatan Pendapatan Petani Hutan Kemasyarakatan - Romi Permana; Ali, Helmi (ASOSIASI IDEBAHASA KEPRI, 2024)
UPTD KPHL Fifty Cities (Unit III) is located in the Payakumbuh City government administrative area, Jalan Rangkayo Rasuna Said No. 58, Balai Nan Tuo, East Payakumbuh District, Payakumbuh City, West Sumatra, 26218. The aim of this research is to build a Perception Relationship Model And Group Dynamics on Forest Conservation and Increasing the Income of Community Forest Farmers (Case Study of Community Forest Groups in UPTD KPHL Fifty Cities). The method used is an analytical or reception survey with data analysis techniques of outer model testing, inner model testing and hypothesis testing. The sample was 95 members of community forestry at UPTD KPHL Limapuluh Kota. The results obtained show that there is a positive and significant influence on the perception of the HKm group on forest conservation in the Community Forest at UPTD KPHL Limapuluh Kota. There is a positive and significant influence of HKm group dynamics on forest conservation in Community Forests in UPTD KPHL Limapuluh Kota. There is a positive and significant influence on the perception of the HKm group on farmers' income in the Community Forest at UPTD KPHL Limapuluh Kota. There is a positive and significant influence of HKm group dynamics on farmers' income in Community Forests in UPTD KPHL Limapuluh Kota. There is a positive and significant influence of forest conservation on farmers' income in Community Forests at UPTD KPHL Limapuluh Kota. There is a positive and significant relationship between the perception of HKm groups, the dynamics of HKm groups and forest conservation together on farmers' income in Community Forests in UPTD KPHL Limapuluh Kota. Keywords— perception of hkm groups, dynamics of hkm groups, forest conservation and farmer income.